Tinjauan Yuridis Perencanaan Sistem Restorative Justice Dalam Penanganan Tindak Pidana Anak - Pranito, Benny; Maryani, Halimatul (Albayan Journal of Islam and Muslim Societies, 2024)
This study aims to examine the role and contribution of law enforcement officers in the planning and implementation of the restorative justice system for children involved in criminal offenses. In addition, the research method employed is normative juridical and empirical legal research. Data were obtained through data collection, literature study, and field research. The research findings indicate the continued dominance of the retributive approach in the legal culture of law enforcement, despite the increasing introduction of restorative justice. The retributive (punitive) approach still prevails in the legal mindset of Indonesian authorities. Many officers tend to impose punishment as the primary means of resolving cases, without considering rehabilitation or the restoration of social relationships.The implementation of the restorative justice system in handling juvenile criminal cases in Indonesia emerged from an urgent need to replace the conventional judicial approach, which tends to be punitive and neglects the developmental aspects of children. Factors such as children's psychological immaturity, the importance of protecting children's rights, and the negative impact of detention on a child's future strongly support the necessity of a more participatory and rehabilitative approach. This system is also driven by national regulations, such as the Juvenile Criminal Justice System Law (UU SPPA), and the demands of international conventions, such as the Convention on the Rights of the Child (CRC).